Prospection of lectins present in the seeds of Bauhinia subclavata Benth and Crotalaria spectabilis Roth - Farias, Alana Alves; Silva, Elda Nunes da; Oliveira, Wilian Rosário de; Rego, Evandro José Lima (Seven Editora, 2023)
A signaling cell is the basis for the triggering of many cellular processes. Among the molecules that mediate these mechanisms are simple carbohydrates or conjugates making up the cell surface membrane receptors and the other proteins, particularly lectins, which would act by binding to these receptors to mediate different activities of cellular metabolism. In this study, we verified the ability of protein extracts obtained from seeds of Bauhinia subclavian, Benth, and Crotalaria spectabilis, Roth to recognize receptors present on human erythrocytes, promote the agglutination of these cells. DOI:https://doi.org/10.56238/alookdevelopv1-023